Modos de vida e conflitos pelo uso dos recursos naturais na Comunidade do Cumbe, Aracati, Ceará - Brasil - Chaves, Leilane Oliveira (2019)
Many of the communities found on the coast of the state of Ceará, in northeastern Brazil, depend on the exploitation of natural resources, fishing, and raising livestock for their livelihood. However, investment in development projects and infrastructure has increasingly threatened the subsistence of these communities. This scenario is exemplified by the community of Cumbe, located in the municipality of Aracati, in Ceará. Cumbe is a traditional fishing community made up of 168 families that has suffered a series of transformations, beginning with the installation of shrimp farming operations in its mangrove sector, in 1998, and the subsequent construction of a wind farm on its dune fields, in 2008. These processes have transformed land occupation and use within the territory of the community. The present study evaluated how the processes of land appropriation necessary for the installation of these projects affected the means of subsistence of the family groups from Cumbe. The first step in this study was the assessment of the principal components of the subsistence of the local residents, through a livelihood approach. This approach was complemented with empirical data obtained through a participant observation approach, the application of 23 questionnaires, and 3 open- ended interviews, through which the principal forms of subsistence (resources, income, and activities) were identified, as well as the effects of the installations of the projects, and the perceptions and assessment of the families with regard to the impacts of the projects on their means of subsistence. The study found that (a) insecurity on land tenure, a common feature of traditional communities, results in the exclusion of residents from the decision-making process on where, when, and how a project will be installed, (b) from land to sea, practices were observed that guarantee sources of income and subsistence for the resident families, which are frequently supplemented by financial resources such as the family supplements and pensions, (c) the impacts caused by the projects had differentiated effects, depending on the distinct modes of exploitation of natural resources by the local residents and their relationships with the projects, and (d) 86 families defined themselves as quilombolas in 2010, emerges as a way of claiming the right to traditionally occupied territory, as a strategy to mediate the degradation of natural resources by the projects and to reconstruct the history of the community. This self- definition was also reflected in a greater degree of rejection of the projects, and contributed to a more cohesive political organization of the residents. Overall, the projects installed in the study area represent a threat to the material and symbolic bonds between the members of the Cumbe community and their territory and its natural resources. Differentiated perspectives on the same territory reflect the different types of land use and appropriation. In this respect, the present study contributes to the expansion of both national and international perspectives on the livelihoods of populations in coastal areas, as well as contributing to an increase in awareness on the territorial conflicts faced by traditional Brazilian populations.